A Biomimetic Alternative to Synthetic Hydroxyapatite: "Boron-Containing Bone-Like Hydroxyapatite" Precipitated From Simulated Body Fluid. Issue 3 (September 2017) - Calis, Mert; Demirtas, Tugrul Tolga; Vatansever, Alper; Irmak, Gulseren; Sakarya, Ahmet Hamdi; Atilla, Pergin; Ozgur, Figen; Gumusderelioglu, Menemse
Abstract : Background: Biological hydroxyapatite (HA), has several mechanical and physical advantages over the commercially available synthetic apatite (CAP-HA). The aim of this in vivo study was to investigate the effect of osteoinductive "bone-like hydroxyapatite" obtained from simulated body fluid (SBF) combined with osteoinductive "boron" (B) on bone healing. Materials: Bone like nanohydroxyapatite (SBF-HA) was precipitated from 10× simulated body fluid (10×SBF). Thirty Sprague-Dawley rats were randomly divided into 5 experimental groups (n = 6 each). The groups were involving blank defect, chitosan, SBF-HA, SBF-HA/B, and CAP-HA. Two biparietal round critical sized bone defect was created using a dental burr. The rats were sacrificed respectively at the end of second and fourth months after surgery and their calvarium were harvested for further macroscopic, microtomographic, and histologic evaluation. Results: The SBF-HA/B group demonstrated the highest mineralized matrix formation rates (30.69 ± 3.73 for the second month, 62.68 ± 7.03 for the fourth month) and was significantly higher than SBF-HA and the CAP-HA groups. The SBF-HA/B group demonstrated the highest mineralized matrix formation rates (30.69 ± 3.73 for the second month, 62.68 ± 7.03 for the fourth month) and was significantly higher than SBF-HA and the CAP-HA groups. In means of bone defect repair histologically, the highest result was observed in the SBF-HA/B group ( P < 0.001). Conclusions: The "bone-like hydroxapatite" obtained from simulated body fluid is worth attention when both its beneficial effects on bone healing and its biological behavior is taken in consideration for further bone tissue engineering studies. It appears to be a potential alternative to the commercially available hydroxyapatite samples.